Exploration of multicultural counseling services to support adolescents' cultural awareness in schools - Alamsyah, Muh. Nur; Muslihati, Muslihati; Peng, Yang (ProGCouns: Journal of Professionals in Guidance and Counseling, 2024)
Cultural awareness in schools is increasingly important in the face of the impact of globalization, especially in promoting an understanding of homogenization, national culture and the influence of consumerism. The ability to adapt in diverse cultural contexts is a key skill in the current era of globalization, where this phenomenon is changing our interactions, work and lifestyles. Multicultural awareness is key to understanding, appreciating and responding to cultural diversity in various contexts, as well as being the foundation for developing inclusive attitudes and improving the quality of interactions between individuals in schools. This study used a systematic literature review with 12 journals (shorted from 98 articles) to find multicultural counseling services that increase cultural awareness in adolescents. The study followed three stages of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA): identification of the records, screening for possible eligibility, and inclusion of the studies. The results of this study showed that the implementation and development of cultural awareness in multicultural counseling services was an important step to create an inclusive educational environment for students from various cultural backgrounds. Multicultural counseling strategies involve a holistic approach to promote understanding and appreciation of cultural diversity. Training counselors in cultural awareness is also important to increase the effectiveness of counseling services. Future research is expected to explore more deeply the role of counselors' cultural awareness in improving interactions with students from different cultural backgrounds and its impact on service quality and student outcomes.